Faktor-Faktor yang Memengaruhi Kualitas Hidup Pasien Gagal Jantung Kronik Fraksi Ejeksi Terjaga (HFpEF) Rawat Jalan di RSUPN Dr. Cipto Mangunkusumo - Pratama, Derin Anugrah; Nasution, Sally Aman; Muhadi, Muhadi; Mansjoer, Arif; Alwi, Idrus; Purnamasari, Dyah; Lydia, Aida; Tahapary, Dicky Levenus (Jurnal Penyakit Dalam Indonesia, 2024)
Introduction. The prevalence of heart failure in Indonesian adults is 1.5%, at least half of which categorized as heart failure with preserved ejection fraction (HFpEF). Quality of life assessment plays an important role in the management of heart failure, one of the tools widely used is the Minnesota Living with Heart Failure (MLHF) questionnaire. In Indonesia, there is still no data regarding risk factors that affect the quality of life of HFpEF patients. This study aimed to determine the quality of life profile of HFpEF patients and the relationship between the risk factors (age, hypertension, DM, smoking, and obesity) on the quality of life of HFpEF patients. Methods. A cross-sectional study was conducted. Data was collected from adult HFpEF (based on echocardiography in the last 6 months) patients (>18 years old) who visited the Cardiology Clinic at Cipto Mangunkusumo Hospital from January 2022 to December 2023. Quality of life was measured using the MLHF questionnaire. Bivariate analysis was performed to find the relationship between risk factors (age, gender, hypertension, DM, smoking, and obesity) and patients’ quality of life. Multivariate analysis was performed for hypertension, DM, gender, and age variables. Results. Out of 206 subjects, 72.33% of patients were dominant in the physical domain items, and 27.67% of patients were dominant in the emotional domain items. The majority of patients dominant in physical items had overall good quality of life. The majority of patients dominant in emotional items also had good quality of life. No significant relationship was found between the dominant domain item and the quality of life in HFpEF patients. We also found that there was no significant relationship between socio-demographic factors and risk factors for dominant domain items. However, there was a significant relationship between age (p=0.005), gender (p=0.001), and smoking history (p=0.001) with the quality of life in HFpEF patients. Adult patients had a poorer quality of life compared to elderly patients (OR= 0.33 [95% CI 0.17-0.66]). No significant relationship was found between hypertension, diabetes mellitus, dyslipidemia, and obesity with the quality of life in HFpEF patients. Conclusions. There is a statistically significant relationship between age, gender, and smoking history with the quality of life in HFpEF patients. Meanwhile, there is no significant relationship between hypertension, diabetes mellitus, and obesity with the quality of life in HFpEF patients.